Sustainable competitiveness and responsible innovations – the case of the European Union countries - Cheba, Katarzyna; Szopik-Depczyńska, Katarzyna (Zrównoważona konkurencyjność i odpowiedzialne innowacje – przypadek krajów Unii Europejskiej, 2019)
The main purpose of the study is an assessment of the relationships between sustainable competitiveness of the economy, sustainable development and responsible innovations. For this purpose the indicators from the 2030 Agenda and data published by OECD describing the concept of green growth were used. The results were obtained on the basis of a two-stage procedure. In the first step the rankings of the EU countries in each the considered areas were calculated and in the second one the results of the previous stage were used to create typological groups with the application of correspondence analysis. The outcomes presented in the paper clearly confirm the significant level of differentiation of the results achieved by EU countries in various areas that make up the overall concept of sustainable competitiveness. The value added of the paper comes from the approaches to the evaluation of the relation between various areas sustainable competitiveness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 139-150
Keywords: sustainable competitiveness; sustainable development; green growth; multidimensional analysis; responsible innovations; zrównoważona konkurencyjność; zrównoważony rozwój; zielony wzrost; analiza wielowymiarowa; odpowiedzialne innowacje